2000
DOI: 10.1002/(sici)1096-8628(20000207)96:1<53::aid-ajmg11>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the serotonin transporter gene linked polymorphism (5-HTTLPR) in anorexia nervosa

Abstract: Previous studies have demonstrated aberrant expression of serotonin in individuals with an eating disorder. Given this the serotonin transporter gene (5-HTT) is a strong candidate to contribute to the genetic component of the aetiology of eating disorders. To determine the role of this particular gene in the susceptibility to anorexia nervosa (AN) we have examined a tandemly repeated sequence close to the promotor region of the 5-HTT gene, which is represented by a long (L) and short (S) variant. Previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…We also did not observe the increased S allele frequency seen in case-control study AN patients possibly due to clinical and/or genetic heterogeneity, variability of linkage disequilibrium between the 5-HTTLPR and another susceptibility allele in different samples, or population stratification affecting the case-control findings. Supporting population stratification, S allele frequencies in case-control study controls (Di Bella et al, 2000;Sundaramurthy et al, 2000;Fumeron et al, 2001) and in the nontransmitted alleles reported here range from 0.36 to 0.49 (w 2 ¼ 9.48, df ¼ 3, p ¼ 0.024) and S allele frequencies range from 0.11 to 0.70, worldwide (Gelernter et al, 1999). We used the TDT to diminish problems due to population stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also did not observe the increased S allele frequency seen in case-control study AN patients possibly due to clinical and/or genetic heterogeneity, variability of linkage disequilibrium between the 5-HTTLPR and another susceptibility allele in different samples, or population stratification affecting the case-control findings. Supporting population stratification, S allele frequencies in case-control study controls (Di Bella et al, 2000;Sundaramurthy et al, 2000;Fumeron et al, 2001) and in the nontransmitted alleles reported here range from 0.36 to 0.49 (w 2 ¼ 9.48, df ¼ 3, p ¼ 0.024) and S allele frequencies range from 0.11 to 0.70, worldwide (Gelernter et al, 1999). We used the TDT to diminish problems due to population stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Rare variants include a 15-repeat allele (Nakamura et al, 2000) with undetermined effect on transcription. Case-control studies (Di Bella et al, 2000;Sundaramurthy et al, 2000;Fumeron et al, 2001) demonstrate a trend towards increased frequency of the S allele, and S/S or S/L genotypes in AN patients, reaching statistical significance for AN-BP patients once (Di Bella et al, 2000) (p ¼ 0.020, odds ratio 1.9, 95% CI 1.1À3.1). However, the one family-based study (Hinney et al, 1997), which used the transmission disequilibrium test (TDT) (Spielman et al, 1993) and 55 trios (AN child+ parents), provided no evidence for preferential transmission of the S allele as 52 S/L parents transmitted 27 S and 25 L alleles to AN children (p ¼ 0.90).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Our result might be a false positive because the AN sample is small. Nevertheless, in the more recent studies, 8,9 an excess of S allele was found in AN although this was not statistically significant. The discrepancy with Hinney et al 10 could be due to a different selection of patients.…”
mentioning
confidence: 96%
“…For example, while some studies show evidence of association between 5-HTTLPR and depressive symptoms, [5][6][7] others do not. [8][9][10][11] An ambiguous pattern of association also exists for ADHD, [12][13][14][15] with few studies reporting association for eating disorders [16][17][18] or conduct disorders. 19,20 The evidence is also conflicting for schizophrenia.…”
mentioning
confidence: 97%